(untitled) (London, 2002)
The world production of citrus fruit has risen enormously, leaping from forty-five million tons a year to eighty-five million in the last 30 years. Today, the potential applications of their essential oils are growing wider, with nearly 40% of fresh produce processed for industrial purposes.
Keywords: Citrus,Plants, Medicinal; Industrial applications